Analysis of Principal Leadership Strategies in Improving Teacher Performance in SDN Model Terpadu Madani Palu - Topila, Febriana; B.M. Gagaramusu, Yusdin; Firmansyah, Arif (CV Kalimasada Group, 2024)
This research aims to find out what strategies are used by school principal to improve teacher performance at the SDN Model Terpadu Madani Palu. This research uses a qualitative approach with a qualitative descriptive approach. Research subjects are principal and class teacher. The instruments in this research are observation sheets, documentation sheets and interview sheets. The data analysis used in this research is data reduction, data presentation and drawing conclusions. The results of this research show that the principal's strategy in improving teacher performance at the SDN Model Terpadu Madani Palu consists of six indicators, namely: planning supervision, helping to solve teacher problems, assessing teacher performance, supervision of teacher administration, evaluating supervision, and follow-up supervision. The school principal has implemented the supervision program. The inhibiting factor in achieving increased teacher performance is that there are some teachers who do not understand the use of IT-based learning media, but school principal always look for ways, so that these teachers can understand by bringing in trusted sources through workshop activities. It can be concluded that the principal's strategy has met the indicators in improving teacher performance. There fore, as the conclusion it can besaid, the principal has performend his duties as a leader.